A Study on Perception Regarding Ease of doing Business After the Introduction of ARTIFICIAL INTELLIGENCE Among GEN Z in Ahmedabad - Chavda, Shreeya; Gohil, Tilak; Vidani, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the perceptions of Generation Z in Ahmedabad regarding the role of artificial intelligence (AI) in simplifying business operations. This study adopted a convergent approach using questionnaires for quantitative data and group discussions for qualitative data. The results show that Generation Z views AI as a driver of productivity, customer engagement and business process optimization. However, concerns regarding data security and workforce replacement remain key issues